UNDERSTANDING THE USE OF COHESION DEVICES AND COHERENCE IN WRITING - Syahreni Siregar (State Institute for Islamic Studies IAIN of Metro, 2014)
To make sense of the writing, the writer needs to understand the use of cohesion devices and coherence. It is important that writing be coherent as well as cohesive. A text is cohesive if its elements are linked together, and a text is coherent if it makes sense. This paper titled “Understnding the use of Cohesion Devices and Coherence in Writing”. This study is aimed to know and understand the using of cohsion devices and coherence in students‟ writing. To make sense of the writing, the writer needs to understand the use of cohesion devices and coherence. It is important that writing be coherent as well as cohesive. This article discuss the concept of writing, cohesion devices, and coherence. The last, this article describe the importance of understanding the use of cohesion device and coherence in writing.